COMPARISON OF ANTI-PROTEINURIC EFFECTS OF AMLODIPINE AND CILNIDIPINE AS AN ADD-ON DRUG TO BASELINE MEDICATION IN HYPERTENSIVE CHRONIC KIDNEY DISEASE PATIENTS - JAMES, JESMI; JAYAKUMAR, DHANYA; SANKARAN, GOMATHY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study were to compare the anti-proteinuric effects of amlodipine and cilnidipine in individuals with Chronic Kidney Disease (CKD) on baseline medication. Methods: This was a prospective observational study carried out in the Department of Nephrology at Government T.D. Medical College, Alappuzha spanning a duration of 1 year from January 2016 to December 2016. The study encompassed a total of 90 hypertensive CKD patients-45 were administered amlodipine and the remaining 45 were given cilnidipine in conjunction with their existing baseline medications. The inclusion criteria consisted of hypertensive CKD patients aged between 18 and 80 years possessing a Glomerular Filtration Rate (GFR) between 30 and 60 mL/min and exhibiting blood pressure readings surpassing 140/90 mmHg despite receiving a loop diuretic (Tab. Frusemide 80 mg BD), an α-blocker (Tab. Prazosin 10 mg BD) and a β-blocker (Tab. Metoprolol 50 mg BD) for a minimum duration of one month. The key parameters that were monitored were sitting systolic and diastolic blood pressure readings and proteinuria which was evaluated by determining the Urine Protein Creatinine (UPC) ratio using untimed random urine samples. The GFR was calculated utilizing the Cockcroft-Gault formula. Results: The number of patients who improved to stage 3A CKD from stage 3B CKD were more with cilnidipine which indicates its reno-protective action. Amlodipine was seen to have no effect on UPC ratio whereas cilnidipine decreased UPC ratio significantly. Conclusion: Unlike amlodipine, cilnidipine exhibits marked reduction in proteinuria and improved GFR thereby preventing progression of hypertensive CKD patients to end stage renal failure.